Growth Response of Garlic (Allium sativum L.) to the Application of Supermes Liquid Organic Fertilizer Dosage - Hafis Ishak Maulana; Afifatun Nisa; Nurul Huda; Nurlina (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Garlic (Allium sativumL.) is a horticultural commodity with high economic value in Indonesia. For optimal growth and yield, garlic plants require macronutrients and micronutrients from fertilization. Micronutrients can be met, for example, by providing organic liquid fertilizer. This study aims to determine the effect of Supermes Liquid Fertilizer dosage application on garlic plant growth. The garlic varieties planted are local varieties using a 1-factor Randomized Block Design with 6 fertilizer dosage treatments: 1) 0 ml/L; 2) 1 ml/L; 3) 2 ml/L; 4) 3 ml/L; 5) 4 ml/L and 6) 5 ml/L. Supermes liquid organic fertilizer. Each treatment was repeated three times: Garlic Response to Supermes Liquid Fertilizer, therefore, there were 18 treatment trials. The results of the Supermes POC fertilizer dosage application did not show significant differences in plant height and number of leaves. However, there was a significant increase in the number of leaves and plant height at each increase in fertilizer dosage. Further research on the application of Supermes POC dosage with various higher concentrations is needed to obtain superior results.